Biotyping and genotyping (MLVA16) of Brucella abortus isolated from cattle in Brazil, 1977 to 2008. - Sílvia Minharro (Public Library of Science (PLoS), 2013)
Brucellosis is a worldwide distributed zoonosis that causes important economic losses to animal production. In Brazil, information on the distribution of biovars and genotypes of Brucella spp. is scarce or unavailable. This study aimed (i) to biotype and genotype 137 Brazilian cattle isolates (from 1977 to 2008) of B. abortus and (ii) to analyze their distribution. B. abortus biovars 1, 2 and 3 (subgroup 3b) were confirmed and biovars 4 and 6 were first described in Brazil. Genotyping by the panel 1 revealed two groups, one clustering around genotype 40 and another around genotype 28. Panels 2A and 2B disclosed a high diversity among Brazilian B. abortus strains. Eighty-nine genotypes were found by MLVA16. MLVA16 panel 1 and 2 showed geographic clustering of some genotypes. Biotyping and MLVA16 genotyping of Brazilian B. abortus isolates were useful to better understand the epidemiology of bovine brucellosis in the region.